Effect of Closed Kinetic Chain Exercise to Reduce Pain and Increase Functional Ability in Patient with Osteoarthritis Genu - Fadhilah, Siti; Widodo, Agus (Journal of Maternal and Child Health, 2024)
Background: Osteoarthritis genu is a degenerative disease with symptoms of chronic inflammation of the joint cartilage which causes pain, limited movement and function. Closed kinetic chain exercise is an active movement that involves many joints and muscle groups simultaneously. This study aims to analyze the effect of closed kinetic chain exercise on reducing pain and increasing functional ability in osteoarthritis genu. Subjects and Method: Quasi experimental research with a research approach in the form of pretest and posttest with control group design. This study was conducted at RST dr. Soedjono Magelang in May-June 2023. A total of 20 osteoarthritis genu patients were divided into two groups: (1) The intervention group was given closed kinetic chain exercise and (2) The control group was given conventional physiotherapy. Pain level was measured using the Visual Analog Scale (VAS). Functional ability was measured by the Western Ontario and McMaster Osteoarthritis Index (WOMAC). Mean differences between the closed kinetic chain exercise group and the conventional physiotherapy group were analyzed using the independent t-test. Results: Providing closed kinetic chain exercise is effective in reducing the level of silent pain (Effect Size = 1.20; p= 0.014), movement pain (Effect Size= 0.99; p= 0.004), movement pain (Effect Size= 1.37; p= 0.023), and increasing functional ability in osteoarthritis genu patients (Effect Size = 0.10; p= 0.023). Conclusion: Providing closed kinetic chain exercise can reduce pain and increase functional ability in osteoarthritis genu.